Enhanced Expression of NR2B Subunits of NMDA Receptors in the Inherited Glaucomatous DBA/2J Mouse Retina - Ling-Dan Dong; Jie Chen; Fang Li; Feng Gao; Jihong Wu; Yanying Miao; Zhongfeng Wang (Neural Plasticity)
DBA/2J mouse has been used as a model for spontaneous secondary glaucoma. Here, we investigated changes in expression of NMDA receptor (NMDAR) subunits and Cdk5/p35/NMDAR signaling in retinas of DBA/2J mice using Western blot technique. The protein levels of NR1 and NR2A subunits in retinas of DBA/2J mice at all ages (6–12 months) were not different from those in age-matched C57BL/6 mice. In contrast, the protein levels of NR2B subunits, in addition to age-dependent change, significantly increased with elevated intraocular pressure (IOP) in DBA/2J mice at 6 and 9 months as compared with age-matched controls. Moreover, expression of Cdk5, p35 and ratio of p-NR2AS1232/NR2A progressively increased with time in both strains, suggestive of activated Cdk5/p35 signaling pathway. However, the changes in these proteins were in the same levels in both strain mice, except a significant increase of p35 proteins at 6 months in DBA/2J mice. Meanwhile, the protein levels of Brn-3a, a retinal ganglion cell (RGC) maker, remarkably decreased at 9–12 months in DBA/2J mice, which was in parallel with the changes of NR2B expression. Our results suggest that elevated IOP-induced increase in expression of NR2B subunits of NMDARs may be involved in RGC degeneration of DBA/2J mice.